Systems biology and metabolic engineering of Rhodococcus for bioconversion and biosynthesis processes - Donini, Eva; Firrincieli, Andrea; Cappelletti, Martina (Folia microbiologica, 2021)
Rhodococcus spp. strains are widespread in diverse natural and anthropized environments thanks to their high metabolic versatility, biodegradation activities, and unique adaptation capacities to several stress conditions such as the presence of toxic compounds and environmental fluctuations. Additionally, the capability of Rhodococcus spp. strains to produce high value-added products has received considerable attention, mostly in relation to lipid accumulation. In relation with this, several works carried out omic studies and genome comparative analyses to investigate the genetic and genomic basis of these anabolic capacities, frequently in association with the bioconversion of renewable resources and low-cost substrates into triacylglycerols. This review is focused on these omic analyses and the genetic and metabolic approaches used to improve the biosynthetic and bioconversion performance of Rhodococcus. In particular, this review summarizes the works that applied heterologous expression of specific genes and adaptive laboratory evolution approaches to manipulate anabolic performance. Furthermore, recent molecular toolkits for targeted genome editing as well as genome-based metabolic models are described here as novel and promising strategies for genome-scaled rational design of Rhodococcus cells for efficient biosynthetic processes application.
Keywords: genom bakteriální; Metabolic Engineering; systémová biologie; genomika; metabolické inženýrství; Genome, Bacterial; Biodegradation, Environmental; Genomics; Rhodococcus; biodegradace; Systems Biology